ONLINE PHARMA RETAIL IS A PROMISING/UNPROMISING AVENUE: AN INDIAN CONTEXT - R, ALAMELU; R, Amudha; Motha, L Cresenta Shakila; R, Nalini (Asian Journal of Pharmaceutical and Clinical Research, 2016)
To consider the prescription of drugs through online retail is an opportunity or not for the end consumers in an Indian context. This paper described the basic issues and challenges related to online pharma retail in the Indian context through case method. India is among the top six global pharmaceutical producers in the world. The Indian vaccines are exported to 150 countries. India produces 40-70% of the World Health Organization (WHO) demand for Diphtheria-Pertussis-Tetanus and Bacille Calmette-Guérin vaccine and 90% of measles vaccine. Sustained by the amazing success achieved by consumer durables industry in the online space, pharma is the next big sector in India to target consumer online. The growth in the industry has created a great opportunity for the online model for this business. India has now seen pharma players taking the e-commerce route with an intention to offer a solution to a number of problems plaguing the retail pharmacy industry. Though online medicines look like a promising trend today, the business is challenged by regulatory issues. Keywords: Online pharmacy, Online pharma retail, Online medicines, E-pharma retailing.